The value proposition of blockchain technologies and its impact on Digital Platforms. (May 2021) - Zutshi, Aneesh; Grilo, Antonio; Nodehi, Tahereh
Highlights: Blockchain Technology has the potential to significantly impact multiple industries. The key typologies of Blockchain Technologies are analysed through a review. A novel Blockchain Value Proposition Pyramid is presented. Blockchain Value Propositions vary based on their degree of disruptiveness. They can complement the functionalities provided by exiting Digital Platforms. Abstract: Since the last few years there has been a massive spurt of Research on Blockchain Technologies and several attempts at incorporating them for a myriad of Business Applications. Blockchain Technologies promised to bring about decentralized trust having the potential to disrupt digital ecosystems by providing alternatives to centralized storage and management of data. This has the potential to radically transform industries and services through new models of data storage, transparency, tracking, payment systems amongst other advantages. However, Blockchain Technology is designed to provide other Value Propositions beyond decentralized storage, such as innovative crypto economic and investment models and radical new forms of decentralized participative governance models that could lead to the evolution of new generation of Digital Platforms and multi stakeholder business interactions. In this paper, through a systematic literature review, we present a set of key Blockchain Value Propositions and a discussion on how it can complement to the evolution of Digital Platforms and the Collaborative Economy. We also argue that while some of the value propositions are easier to integrate with existing Digital Platforms, more disruptive value propositions such as Business Automation, Economic and Governance Models present greater challenges but could lead to not just innovation at the technological level, but also metamorphosis of the existing social, economic and governance models.